Portability of social security benefits in Malaysia: the need for coordination between Malaysia and labour-sending countries - Mohamad Amin, Noor Shuhadawati; ,; , (2017)
Along with the basic principle of human rights as enshrined in the Universal Declaration of Human Rights, social security law has evolved greatly at the expanse of International Labour Organisation (ILO) through a list of related conventions. These conventions draw no distinction between a local or a migrant worker for the entitlement of benefits and coverage to be granted to the latter under the said law. Interestingly, ILO has also provided that when a migrant worker or his family members leave the country of employment, his right to the benefits should not be automatically removed upon his return to his country or when he moves to another country. The idea is that the benefits received by the workers should basically follow them regardless where they may reside. Nonetheless, certain conditions are established in a country in granting social security to the society including the residency requirements, specifically the duration of residency at a particular country for a person to be entitled to such benefits under social security. To materialise this, countries are expected to integrate the specific standards by ILO into their national systems of social security. Hence, this paper aims to examine the underlying principles in ILO conventions ratified by Malaysia and the possibility of materialising the portability of social security benefits between this country and the labour-sending countries.